Systems Audit for the Tourism Sector - Cuba, Nestor; Pariona, Rosario; Pacheco, Alex; Mendoza, Elizabeth; Espino, Consuelo; Larico, Bertha (The journal of contemporary issues in business and government, 2021)
It is essential to have a Systems Audit process to determine the conformity of the products, processes, plans, agreements and monitoring that may be generated in the Tourism Sector. The objective of the article is to describe a procedure to carry out computer audits, evaluate, determine the level of compliance with the processes and propose improvement actions. For this, we rely on observation sheets, survey format and checklist format of the Peruvian Technical Standard NTP ISO / IEC 27001: 2014, NTP ISO / IEC 12207: 2016 and ISO / IEC 27004: The results show that having a defined process saves management costs, identifies threats and reduces risks while safeguarding the integrity of the data. Highlighting the importance of improvement plans to prevent crime, increase the profitability of operations and scale the business strategy. Likewise, know the non- conformities of the processes so that through corrective and preventive actions they become compliant processes.